26.1%‐efficient POLO‐IBC cells: Quantification of electrical and optical loss mechanisms. (16th January 2019) - Hollemann, Christina; Haase, Felix; Schäfer, Sören; Krügener, Jan; Brendel, Rolf; Peibst, Robby
Abstract: We present experimental results for interdigitated back contacted (IBC) solar cells with passivating POLO contacts for both polarities with a nominal intrinsic poly‐Si region between them. We reach efficiencies of 26.1% and 24.9% on a 1.3 Ω cm and 80 Ω cm p ‐type FZ wafer and 24.6% on a 2 Ω cm n ‐type Cz wafer, respectively. The initially measured implied efficiency potentials of the cells after passivating the surfaces are very similar, namely, 26.8%, 26.8%, and 26.4%, respectively. We attribute the difference between the efficiency potential and the final current‐voltage measurement to degradation, perimeter, and series and shunt resistance losses, which we quantify by lifetime measurements. With these measurements in combination with a finite element simulation, we determine the surface recombination velocity in the nominal intrinsic poly‐Si region to be in the range from 13 to 21 cm s −1 . Using the same approach, we analyze the increase of the front surface recombination velocity during cell processing from 2 to 10 cm s −1 for the 1.3 Ω cm and from 0.5 to 2.3 cm s −1 for the 80 Ω cm. This leads to the fact that cells fabricated on lowly doped bulk material are more vulnerable to a process‐induced degradation of the surface passivation quality. We further determine the theoretical limits of the cells by firstly idealizing the recombination (28% for 1.3 Ω cm and 28.2% for 80 Ω cm) and secondly also idealizing the optics of the solar cells (29.4% and 29.5%). Abstract : We present an experimental and simulation study of POLO‐IBC cells on different wafer materials with the distinct feature of a nominally intrinsic poly‐Si region ( i ‐region), which separates the n ‐type poly‐Si and p ‐type poly‐Si region. With the simulations, we analyze the efficiency potentials in dependence of varying surface recombination velocities of the front and the i ‐regions on the rear side. With this cell concept, we achieve an independently certified efficiency of 26.10 ± 0.31% on p ‐type 1.3 Ω cm wafer material.